2013
DOI: 10.1080/07055900.2013.822787
|View full text |Cite
|
Sign up to set email alerts
|

Stable Carbon Isotope Ratios and the Photochemical Age of Atmospheric Volatile Organic Compounds

Abstract: The dependence of ozone formation on the mixing ratios of volatile organic compounds (VOCs) and nitrogen oxides (NO x ) has been widely studied. In addition to the atmospheric levels of VOCs and NO x , the extent of photochemical processing of VOCs has a strong impact on ozone levels. Although methods for measuring atmospheric mixing ratios of VOCs and NO x are well established and results of those measurements are widely available, determination of the extent of photochemical processing of VOCs, known as phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…For the range of carbon 10 isotope ratios observed in ambient studies uncertainties of the rate constants and kinetic isotope 11 effects known from laboratory studies result in uncertainty of nitrophenol carbon isotope ratios 12 typically less than ± 0.5 ‰, which is similar to or below the estimated accuracy of ambient 13 measurements of nitrophenol carbon isotope ratios (Saccon et al, 2013;Saccon et al, 2015). 14 reports that 25 % of PCA derived from carbon isotope ratio measurements of benzene and 9 toluene are below 1.1×10 11 s molecules cm -3 and 1.6×10 10 s molecules cm -3 , respectively.…”
Section: Pca From Mass Balance 15mentioning
confidence: 98%
See 2 more Smart Citations
“…For the range of carbon 10 isotope ratios observed in ambient studies uncertainties of the rate constants and kinetic isotope 11 effects known from laboratory studies result in uncertainty of nitrophenol carbon isotope ratios 12 typically less than ± 0.5 ‰, which is similar to or below the estimated accuracy of ambient 13 measurements of nitrophenol carbon isotope ratios (Saccon et al, 2013;Saccon et al, 2015). 14 reports that 25 % of PCA derived from carbon isotope ratio measurements of benzene and 9 toluene are below 1.1×10 11 s molecules cm -3 and 1.6×10 10 s molecules cm -3 , respectively.…”
Section: Pca From Mass Balance 15mentioning
confidence: 98%
“…However, partitioning will influence the loss rate for SVOC since it is assumed that there 12 is little to no chemical loss in the PM phase. Furthermore, uncertainty in phase partitioning will 13 only result in minor uncertainties of the photochemical nitrophenol loss rate since it has been 14 reported that only approximately 20 % of the nitrophenols partition into the particle phase 15 (Saccon et al, 2013(Saccon et al, , 2015. 16 There are also some reaction rate constants which for which no laboratory measurements 17 are available.…”
Section: Pca From Mass Balance 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Details about the sampling site can be found in Kornilova et al, 2013. This paper also contains a detailed discussion of the use of the measured VOC carbon isotope ratios to quantitatively evaluate photochemical VOC processing.…”
Section: Ambient Measurementsmentioning
confidence: 99%
“…The newly developed method was applied in an ambient air quality field study in 2009 to 2010 (Kornilova et al, 2013) at Egbert, a semi-rural location in southern Ontario. Details about the sampling site can be found in Kornilova et al, 2013.…”
Section: Ambient Measurementsmentioning
confidence: 99%